Reconstruction of primitive-shaped pipe elbows from a triangular mesh in ship outfitting model - Na, Gun Yeol; Yang, Jeongsam; Mun, Duhwan; Cheon, Sanguk (Journal of Mechanical Science and Technology, 2021)
Integration of heterogeneous computer-aided design (CAD) models into shipbuilding CAD systems is necessary during ship modeling in shipyards. Vendor package models provided by equipment vendors were designed using mechanical CAD systems. Complex triangular meshes severely affect the modeling performance of shipbuilding CAD systems. Particularly, reconstructing pipe elbows from shipbuilding CAD models represented by triangular meshes is a challenging problem. We present a method to reconstruct elbow primitives for plant design management system (PDMS), a commercial shipbuilding CAD system, from a triangular mesh using mesh segmentation and elbow parameter extraction method. The mesh segmentation method divides a mesh of irregular and minimal 3D points into segments for elbow parameter extraction based on curvature and connectivity. The proposed method also extracts the parameters of an elbow using the geometric features of a partial torus. The results of the proposed method are implemented and verified using 100 test models.
Keywords: Computer aided design systems; Curvature-based segmentation; Design systems; Elbow fitting; Parameters extraction; Partial torus; Plant design system; Plant designs; Ship outfitting model; Triangular meshes; Curvature-based segmentation; Elbow fitting; Parameter extraction; Partial torus; Plant design system; Ship outfitting model